Anemia and its effect on thyroid profile in pregnant women in tertiary care centre - Singh, Rishita; Gupta, Smriti; Tyagi, Mamta; Gupta, Manvi; Yadav, Sandeep Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: According to WHO, highest incidence of anaemia is seen in Asia with about half of the anaemic women present in Indian subcontinent only. Various studies in the past have reported that iron deficiency hampers thyroid function. The thyroid hormones are essential for both foetal and maternal well-being. Our aim was to study anemia among pregnant women and its effect on thyroid profile. Methods: In this prospective observational cohort study 200 women were enrolled (100 anemic and 100 non anemic) and subsequent thyroid profile was done. Confounders like high risk pregnancy, chronic diseases like coronary heart disease, renal failure/insufficiency, liver disease, Astro-intestinal diseases, known cases hypothyroidism was excluded. The women were followed up till delivery. The data was be tabulated and analysed using Chi square test in case of qualitative data and student t test in case normally distributed quantitative data. Results: Four percentages of pregnant women had overt hypothyroidism in anemic group as compared to 3% in non-anemic group. 35% in anemic group had sub-clinical hypothyroidism as compared to 16% in non-anemic group and the difference was statistically significant. The comparison of TSH values in anemic and non anemic women was statistically significant (p=0.002). There was no association found with severity of anemia with TSH, ft3, ft4 values. Conclusions: The present study found a significant association between anemia and hypothyroidism. However thyroid dysfunction was not associated with the severity of anemia. Further studies are warranted to directly identify the causal relationship between the two.